Intellectual Capital and Firm Performance across Pakistani Industries - Ahmad, Muhammad; Rus, Rohani Mohd (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study sheds light on the differences in intellectual capital (IC) efficiencies across non-financial sectors in Pakistan and determines the relationship between IC and firm performance. The study used sample of 155 non-financial firms from the manufacturing and service industries of Pakistan for the period 2009-2018. This study contributes to IC research by applying modified value-added intellectual capital (MVAIC) model with relationship to firm performance (return on assets and Tobin’s Q) of Pakistani non-financial firms which was overlooked by the previous researchers. In addition, to deal with endogeneity, the dynamic panel generalized methods of moments regression is applied to test the relationship between IC and performance. Findings provide evidence that different sectors in non-financial industries manage IC components differently. IC increases both market-based performance and accounting-based performance of Pakistani firms. Among all IC components, human capital efficiency is an important determinant of firm performance. The implications can provide help managers and investors to understand the IC to increase the firm performance.